Native and Immigrant Entrepreneurship. Lessons for Local Liabilities in Globalization from the Prato Case Study - Ceccarelli, Diego (Piccola Impresa / Small Business, 2019)
This book review explain how the authors adopts a multidisciplinary approach to the issue of liabilities of native and immigrant entrepreneurship in local contexts. The volume discusses the idea that in today’s global economy, belonging to global networks is increasingly more important than being members of the dominant group in the national market. In addition, the phenomenon of globalization not only creates “bridges” between distant places but also changes the face of businesses and socioeconomic systems at the local level. These aspects affect social and business networks and are strongly linked to the study of business communities settled in different territories.